(untitled) (One Health Journal of Nepal, 2023)
Antimicrobial resistance (AMR) is a continuously growing and substantial threat of the twenty-first century to global health and development and its convergence with the current COVID-19 pandemic poses even a worse impact to population health. This viewpoint focuses on combined impact and determinants of AMR and Covid-19 on population health. Furthermore, it outlines potential procedures and interventions to moderate the burden of worldwide AMR in current and future pandemics.